Expression of ABA signalling genes and ABI5 protein levels in imbibed Sorghum bicolor caryopses with contrasting dormancy and at different developmental stages - Rodríguez, María Verónica (2009)
Background and AimsPre-harvest sprouting susceptibility in grain sorghum (Sorghum bicolor) is related to low seed dormancy and reduced embryo sensitivity to inhibition of germination by abscisic acid (ABA). Intra-specific variability for pre-harvest sprouting might involve differential regulation of ABA signalling genes.MethodsSorghum genes encoding homologues for ABA signalling components from other species (ABI5, ABI4, VP1, ABI1 and PKABA1) were studied at the transcriptional and protein level (ABI5) during grain imbibition for two sorghum lines with contrasting sprouting phenotypes and in response to hormones.Key ResultsTranscript levels of these genes and protein levels of ABI5 were higher in imbibed immature caryopses of the more dormant line. Dormancy loss was related to lower transcript levels of these genes and lower ABI5 protein levels in both genotypes. Exogenous ABA inhibited germination of isolated embryos but failed to prevent ABI5 rapid decrease supporting a role for the seed coat in regulating ABI5 levels.ConclusionsSeveral genes involved in ABA signalling are regulated differently in imbibed caryopses from two sorghum lines with contrasting pre-harvest sprouting response before - but not after - physiological maturity. A role for ABI5 in the expression of dormancy during grain development is discussed.